ANALISIS KEPUASAN PENGGUNA LIVE CHAT BPS SUMATERA BARAT MENGGUNAKAN MODEL DELONE MCLEAN - Imansyah Fadhil Fidri; Elfi Tasrif (Universitas Negeri Padang, 2019)
Live chat is a message service via text message, where users can ask operators about certain information. The Central Statistics Agency of West Sumatra Province has a live chat service on its website. This study aims to determine the level of data user satisfaction with the live chat service, and to find out how much influence the live chat service on the BPS West Sumatra website uses the Delone and McLean model. The variables in this study are Information Quality, System Quality, and Service Quality as the independent variable, and User Satisfaction as the dependent variable. This study uses a questionnaire as a data collection tool with a Likert scale. Data processing methods used include validity, reliability, normality, linearity, and multiple linear regression tests. The results showed that the information quality and system quality variables had a positive and significant effect on user satisfaction, but the service quality variable did not significantly influence user satisfaction.Keywords:Information quality, system quality, service quality, user satisfaction